Liberalization and the public sector; the pre-eminent role of governments in the `sale' of higher education abroad - Dodds, Anneliese (2009)
Much recent scholarship concerning liberalization has emphasized the role of regulates, rather than governments, in promoting liberalization. This article examines such scholarship in the light of an important development in the British and French public sectors - the creation of new agencies (the Education Counselling Serice and EdulFrance) to `sell' British and French higher education to potential international students. The new agencies attempted to induce two things: competition amongst higher education institutions for the recruitment of international students from developed and emerging economy countries, and the commodification of these students. This article shows that, contrary to existing theories of liberalization, governments were pre-eminent in pushing forward this liberalization, while higher education institutions attempted to hold it back. - Reproduced.
Keywords: Public sector; Liberalization; Higher education